PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) BONE DALAM PERSPEKTIF INDIKASI GEOGRAFIS - Irma Nur Yumna; Hasbir Paserangi; Marwah Marwah (UNES Law Review, 2023)
Protection of the laws of intellectual property of the coconut oil bone in a geographical point of view (guided by paserangi and marwah). The purpose of this study is: to know, understand and analyze (i) how the character is present in pure bone coconut oil (vco) so that it is potentially protected intellectual property rights (geographic indications) and (ii) to know, understand and analyze the efforts of local governments and communities in promoting the legal protection of pure bone coconut oil (VCO). The kind of research carried out using empirical research methodology conducted interviews with primary source of information and data collection of craftsman ( vco ) pure coconut oil, the district government bone and the ministry of justice and human rights south sulawesi. The results of this study show that: (i) pure coconut oil ( vco) bone potential to register geographical indications for having a reputation, the quality and characteristic of its distinctive flavor.Based on a pure coconut oil laboratory test ( vco ) bone meets 5 (five) parameters to register geographical indications, which is the content of 81854 fatty acid, peroxide number 0.4996, Burial number 210.92 mg koh/gr, shit number 0.0002 %, and water number 0.1908 %. The government of the bone district is expected to make an effort to register geographically on pure coconut oil (Vco) as a step in order to obtain legal protection and legal certainty as well as to obtain exclusive rights and economic benefits, As set up in the 20-year law of 2016 about brands and geographical indications.